Nuclear interactor of ARF and Mdm2 regulates multiple pathways to activate p53 - Reed, Sara M (Landes Bioscience, 2014)
The p53 tumor suppressor is controlled by an interactive network of factors that stimulate or inhibit its transcriptional activity. Within that network, Mdm2 functions as the major antagonist of p53 by promoting its ubiquitylation and degradation. Conversely, Tip60 activates p53 through direct association on target promoters as well as acetylation of p53 at lysine 120 (K120). This study examines the functional relationship between Mdm2 and Tip60 with a novel p53 regulator, NIAM (nuclear interactor of ARF and Mdm2). Previous work showed NIAM can suppress proliferation and activate p53 independently of ARF, indicating that other factors mediate those activities. Here, we demonstrate that NIAM is a chromatin-associated protein that binds Tip60. NIAM can promote p53 K120 acetylation, although that modification is not required for NIAM to inhibit proliferation or induce p53 transactivation of the p21 promoter. Notably, Tip60 silencing showed it contributes to but is not sufficient for NIAM-mediated p53 activation, suggesting other mechanisms are involved. Indeed, growth-inhibitory forms of NIAM also bind to Mdm2, and increased NIAM expression levels disrupt p53–Mdm2 association, inhibit p53 polyubiquitylation, and prevent Mdm2-mediated inhibition of p53 transcriptional activity. Importantly, loss of NIAM significantly impairs p53 activation. Together, these results show that NIAM activates p53 through multiple mechanisms involving Tip60 association and Mdm2 inhibition. Thus, NIAM regulates 2 critical pathways that control p53 function and are altered in human cancers, implying an important role for NIAM in tumorigenesis.